Omnes viae Albam ducunt. Z badań nad pograniczem pomorsko-wielkopolskim we wczesnym średniowieczu - Chudziak, Wojciech (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
The article touches upon the emergence of settlement structures in the West Pomerania Lakeland including the upper estuary of the Rega and the Parsęta as well as the Drawa and the Gwda, frequently referred to as the borderland between Pomerania and Wielkopolska. An attempt was made to assign periods to settlement developments with respect to the emergence of the borderland. Special emphasis was placed on central locations like strongholds and some islands as well as far-reaching routes leading to Białogard (Alba in Latin).